Highly crystalline nickel hexacyanoferrate as a long-life cathode material for sodium-ion batteries. Issue 45 (21st July 2020) - Rehman, Ratul; Peng, Jian; Yi, Haocong; Shen, Yi; Yin, Jinwen; Li, Chang; Fang, Chun; Li, Qing; Han, Jiantao
Abstract : A low-speed synthesis strategy was designed to fabricate Prussian blue analog based electrode materials for high-performance rechargeable batteries. Abstract : Prussian blue analogs (PBAs) are attractive cathode candidates for high energy density, including long life-cycle rechargeable batteries, due to their non-toxicity, facile synthesis techniques and low cost. Nevertheless, traditionally synthesized PBAs tend to have a flawed crystal structure with a large amount of [Fe(CN)6 ] 4− openings and the presence of crystal water in the framework; therefore the specific capacity achieved has continuously been low with poor cycling stability. Herein, we demonstrate low-defect and sodium-enriched nickel hexacyanoferrate nanocrystals synthesized by a facile low-speed co-precipitation technique assisted by a chelating agent to overcome these problems. As a consequence, the prepared high-quality nickel hexacyanoferrate (HQ-NiHCF) exhibited a high specific capacity of 80 mA h g −1 at 15 mA g −1 (with a theoretical capacity of ∼85 mA h g −1 ), maintaining a notable cycling stability (78 mA h g −1 at 170 mA g −1 current density) without noticeable fading in capacity retention after 1200 cycles. This low-speed synthesis strategy for PBA-based electrode materials could be also extended to other energy storage materials to fabricate high-performance rechargeable batteries.